A home for xenophobia: U.S. public housing policy under Trump. Issue 1 (2nd January 2021) - Allen, Ryan; Goetz, Edward G.
Abstract: Elected after espousing xenophobic rhetoric and policy proposals, President Donald Trump has pursued an anti-immigrant approach to governance that spans multiple areas of policy and practice in the U.S., including public housing. In this essay, we argue that the Trump Administration has pursued a variety of egregious examples of xenophobic policies, but far from anomalies, these actions are in keeping with the long historical tradition of xenophobia in the U.S. In the area of public housing, policy changes that seek to exclude some immigrants and their families from living in public housing allow the administration to pursue two goals simultaneously. First, it signals to President Trump's base supporters that he is following through on his 'America First' campaign promises. Second, it allows the Trump Administration to frame the debate around the deservingness of tenants using public housing, distracting the public from the continuing disinvestment in this public benefit during an affordable housing crisis in the U.S.